Development of titanium dioxide nanowire incorporated poly(vinylidene fluoride–trifluoroethylene) scaffolds for bone tissue engineering applications - Anitha Augustine (14151195) (2019)
Critical size bone defects that do not heal spontaneously are among the major reasons for the disability in majority of people with locomotor disabilities. Tissue engineering has become a promising approach for repairing such large tissue injuries including critical size bone defects. Three-dimension (3D) porous scaffolds based on piezoelectric polymers like poly(vinylidene fluoride-trifluoroethylene) (P(VDF-TrFE)) have received a lot of attention in bone tissue engineering due to their favorable osteogenic properties. Owing to the favourable redox properties, titanium dioxide (TiO2) nanostructures have gained a great deal of attention in bone tissue engineering. In this paper, tissue engineering scaffolds based on P(VDF-TrFE) loaded with TiO2 nanowires (TNW) were developed and evaluated for bone tissue engineering. Wet-chemical method was used for the synthesis of TNW. Obtained TNW were thoroughly characterized for the physicochemical and morphological properties using techniques such as X-Ray diffraction (XRD) analysis and transmission electron microscopy (TEM). Electrospinning was used to produce TNW incorporated P(VDF-TrFE) scaffolds. Developed scaffolds were characterized by state of art techniques such as Scanning Electron Microscopy (SEM), XRD and Differential scanning calorimetry (DSC) analyses. TEM analysis revealed that the obtained TiO2 nanostructures possess nanofibrous morphology with an average diameter of 26 ± 4 nm. Results of characterization of nanocomposite scaffolds confirmed the effective loading of TNW in P(VDF-TrFE) matrix. Fabricated P(VDF-TrFE)/TNW scaffolds possessed good mechanical strength and cytocompatibility. Osteoblast like cells showed higher adhesion and proliferation on the nanocomposite scaffolds. This investigation revealed that the developed P(VDF-TrFE) scaffolds containing TNW can be used as potential scaffolds for bone tissue engineering applications. Other Information Published in: Journal of Materials Science: Materials in Medicine License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10856-019-6300-4